Clinical and Visual Outcomes of Transepithelial Photorefractive Keratectomy After Myopic Correction in A Private Clinic in Benghazi Using Schwind Amaris - Mostafa El Awami; Hamad Elzarrug (AlQalam Journal of Medical and Applied Sciences, 2024)
This study aimed to assess the results of correcting myopia with transepithelial photorefractive keratectomy (TransPRK) performed using the Schwind Amaris Machine. A total of 44 eyes have been included in this prospective study. The preoperative sphere was between (-1.25 and -8.00 DS), while the preoperative cylinder dioptres varied from (-0.75 to -5.00 DC). Before surgery and three months later, measurements were conducted to evaluate uncorrected (UDVA) and corrected (CDVA) distance visual acuity. The study focused on both clinical and visual outcomes. Following Three months after TransPRK, the included eyes had an uncorrected distance visual acuity better than or the same as preoperative CDVA; no patient showed loss of two lines; 31.8% (14 eyes) maintained the same level; 54.5% (24 eyes) improved by one line; 11.3% (five eyes) improved by two lines; and the remaining 2.2% (one eye) had a decrease of one line. The slit lamp exam post-operatively shows complete epithelial healing within five days, but only 4.35% (one candidate) show grade 1 central haze. TransPRK is a reliable and effective option for managing myopia safely. تهدف هذه الدراسة إلى تقييم نتائج تصحيح قصر النظر من خلال عملية استئصال القرنية الضوئية الانكسارية عبر الظهارة التي يتم إجراؤها باستخدام آلة شويند أماريس. تم تضمين ما مجموعه 44 عينًا في هذه الدراسة المستقبلية. كانت كرة ما قبل الجراحة بين (-1.25 و-8.00 DS)، في حين تراوحت ديوبتر الأسطوانة قبل الجراحة من (-0.75 إلى -5.00 DC). قبل الجراحة وبعد ثلاثة أشهر، أجريت قياسات لتقييم حدة البصر عن بعد غير المصححة والمصححة. ركزت الدراسة على النتائج السريرية والبصرية. بعد مرور ثلاثة أشهر على استئصال القرنية الضوئية الانكسارية عبر الظهارة، كان للعينين المشمولتين حدة بصرية غير مصححة أفضل من أو مماثلة لحدة البصر عن بعد المصححة قبل الجراحة؛ لم يظهر أي مريض فقدان سطرين. وحافظ 31.8% (14 عيناً) على نفس المستوى؛ 54.5% (24 عينًا) تحسنوا بخط واحد؛ 11.3% (خمس عيون) تحسن بخطين؛ والنسبة المتبقية 2.2% (عين واحدة) كان بها نقصان بمقدار خط واحد. يُظهر فحص المصباح الشقي بعد العملية الجراحية شفاء ظهاري كامل خلال خمسة أيام، لكن 4.35% فقط (مرشح واحد) يظهر ضبابًا مركزيًا من الدرجة الأولى. استئصال القرنية الضوئية الانكسارية عبر الظهارة هو خيار موثوق وفعال لإدارة قصر النظر بأمان